Creation of a refractive lens within an existing intraocular lens using a femtosecond laser - Sahler, Ruth; Bille, Josef F.; Enright, Sean; Chhoeung, Somaly; Chan, Kevin (Journal of cataract and refractive surgery, 2016)
To assess the efficiency and effectiveness of the technology that creates a hydrophilicity-based refractive index change within a standard intraocular lens (IOL) to alter the refractive characteristics of the IOL.
Gesehen am 07.05.2020